Implementation of Sports Habits through Healthy Gymnastics to Create Great Indonesian Children at UPT SDN Sidorejo 1 - Badri Atul Fikriyah; Lilis Sintiya Ningsih; Sayid Husen Des San Wardani; Wendri Wiratsiwi (International Journal of Studies in International Education, 2025)
This article is created as an effort to publish information about the habits implemented by students to form a great Indonesian generation in sports through healthy gymnastics on Tuesday, Wednesday, Thursday, Friday, and Saturday. Additionally, this article discusses the importance of cultivating sports habits from elementary school age to create a healthy and active lifestyle. The method used in this research is a qualitative approach with data collection techniques using library research, where the authors collect various references through journals, articles, and other sources. Gymnastics itself is a type of sport performed en masse, ranging from elementary to high school levels and the general public. In the past, gymnastics was highly cultural, proven by the lack of differences across almost all societal groups - gymnastics was done both in groups and collectively, with young and old, males and females exercising together. This program was also implemented at UPT SDN Sidorejo 1 every day before class, and its results are evident in the emergence of student self-confidence, creative attitudes, and a healthy lifestyle.